Income distribution and differentials of selected barangays in Cabatuan, Iloilo. - Ladrido, Jennifer Mae Ledesma
The study deals with the characterization of the distribution of income and the identification of the sources of income differentials in selected barangays in Cabatuan. The areas under study were chosen purposively, identifying the three barangays which will be affected by the proposed construction of a regional airport facility of international standards. These three barangays are Tiring, Tabucan and Talanghauan. A sample size of 84 respondents were randomly selected from a total household population of 680. The data were culled from the questionnaires gathered by the Ugnayan ng Pahinungod/Oblation Corps program in coordination with the municipality of Cabatuan for the purpose of establishing a data bank for the municipality. The tools used for analysis were the gini ratio, Lorenz curve and linear regression. The study adapted the lognormal transformation of the regression model used in previous studies by Signey Formacion. The results showed that the Lorenz curve distribution of incomes for the three barangays in Cabatuan was less bowed out than the Lorenz curves of the Philippines and Region VI. This indicates that incomes in Cabatuan were more equally distributed than incomes for the Philippines and Region VI in 1994. This finding was confirmed by the values for the gini ratio. The gini ratio for Cabatuan was 0.4038, slightly better than the figures for the gini ratio of the Philippines at 0.4506 and for the Region VI at 0.4064. Eight variables were identified that affect household income. These variables were: primary source of income (PSY), educational attainment of the household head (EDUC), sex of the household head (SEX), age of the household head (AGE), number of alternative sources of income (ASY), household size (SIZE), household labor force (LABOR) and number of household members who are employed (EMP). Dummy variables were used for PSY, EDUC and SEX. The initial regression identified only one significant variable, that of overseas contract as primary source of income. Using the stepwise regression, four variables were found to be significant: professional services as primary source of income, overseas contract work as primary source of income, the number of alternative sources of income and household size. It was recommended based on the results of the study that the government should invest more in education in the area. Furthermore, livelihood programs should be introduced to increase the number of alternative sources of income. Lastly, it was recommended that the government in conjunction with the private sector should already initiate steps in preparing these areas in terms of provision of employment for the proposed airport.